2005
DOI: 10.1523/jneurosci.2648-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped Axon Pruning via Plexin Signaling Is Associated with Synaptic Complex Elimination in the Hippocampus

Abstract: Plexin signaling is required for stereotyped pruning of long axon collaterals in the vertebrate CNS; however, a cellular basis for plexins on stereotyped pruning has not been determined. Using quantitative electron microscopy and immunocytochemistry, we found that infrapyramidal mossy fiber axon collaterals form transient synaptic complexes with basal dendrites of CA3 pyramidal cells in the early postnatal mouse hippocampus. At later postnatal ages, these synaptic complexes stop maturing and are removed before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 52 publications
(87 reference statements)
6
102
0
Order By: Relevance
“…mossy boutons that contact interneurons are generally small in size and contain one synapse. In contrast, the synaptic complexes analyzed in this study are composed of a large presynaptic mossy fiber bouton and postsynaptic dendritic excrescence from a CA3 pyramidal cell with multiple synaptic contacts forming between the two (16,17,29). Given the small percentage of new neurons among all of the existing mature DGCs in the adult hippocampus, unlabeled mossy fiber boutons adjacent to GFP ϩ boutons were analyzed and used as a control for mature bouton structure.…”
Section: Axonal Targeting Of Newborn Dgcs In the Adultmentioning
confidence: 99%
See 2 more Smart Citations
“…mossy boutons that contact interneurons are generally small in size and contain one synapse. In contrast, the synaptic complexes analyzed in this study are composed of a large presynaptic mossy fiber bouton and postsynaptic dendritic excrescence from a CA3 pyramidal cell with multiple synaptic contacts forming between the two (16,17,29). Given the small percentage of new neurons among all of the existing mature DGCs in the adult hippocampus, unlabeled mossy fiber boutons adjacent to GFP ϩ boutons were analyzed and used as a control for mature bouton structure.…”
Section: Axonal Targeting Of Newborn Dgcs In the Adultmentioning
confidence: 99%
“…The changes in bouton structure over development were assessed according to a classic staging paradigm (16,17) (see Methods). Briefly, stage 1 boutons form either no or few synaptic contacts exclusively onto dendritic shafts (nonspinous synaptic contacts), stage 2 boutons have synaptic contacts onto immature dendritic spines (finger-like structures without discernible organelles), and stage 3 boutons have synaptic contacts onto mature dendritic spines containing organelles, with stage 3a boutons having fewer synaptic contacts onto each dendritic spine (Ͻ2 synaptic contacts per spine) than stage 3b boutons (Ն2 synaptic contacts per spine).…”
Section: Axonal Targeting Of Newborn Dgcs In the Adultmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient long IPB is stereotypically pruned back later in development. Electron microscopic analysis suggests that the IPB pruning is mediated by axon branch retraction (Liu et al 2005), and the length of the IPB is reported to be affected …”
Section: Stereotyped Pruning In the Hippocampusmentioning
confidence: 99%
“…Quantitative immuno-electron microscopy has shown that the IPB axons form transient synaptic contacts in their transient target region before they are pruned (Liu et al 2005). The pruning of the IPB is preceded by the elimination of these immature synaptic contacts, which is triggered by the action of Sema3F signaling.…”
Section: Semaphorin Neuropilin and Plexinmentioning
confidence: 99%